Investigation, design and fabrication of miniaturized CMOS novel active RFID tags : Doctor of Philosophy in Engineering-Electronics, Information and Communication Systems at Massey University, Albany campus - Kumari, Meera (Massey University, 2021)
The drastic decline in the bee population in the past few years is alarming given the quantity and quality of global food reliance on these insect pollinators. To ensure sustainable crop production and maintain biodiversity, it has become an important area of research for entomologists to study the factors involved in the dramatic population decline of these tiny insects. Understanding the insect’s biology and their foraging behavior tracking in the agricultural landscape is crucial. However, due to the large size of the available PCB-based tracking tags knowing their true behaviours in the presence of various chemical fertilizers and pesticides is still a challenge. In this research, a very new VHF radio telemeter architecture has been developed which could facilitate tracking of a large number of small insects and bees wirelessly in real-time at a distance of around 1km. The architecture is based on a novel circuit topology to generate an extremely low duty cycle signal digitally which for the first time does not require any passive elements. This digital generation technique of the low duty cycle has made it possible to realize the complete telemeter design on 1mmX 1mm ASIC chip, except for the antenna and the battery, and eliminated the need for discreet components which are mounted on PCB. Due to inconsistent fabrication facilities, the telemeter circuit parts were implemented in CMOS8RF-130nm and 8HPP-28nm, but the final ASIC telemeter prototype is realized in TSMC 65nm process technology and the fabricated chip is experimentally tested in the lab to verify its performance in the manufacturing environment. The design consists of a digital core circuit to generate 8-bit binary-coded 0.0078 duty-cycled burst mode signaling and a full on-chip analog power management circuit to locally generate the required voltage supplies with predefined dependence on temperature for the digital circuitry with the compensation for the temperature variation on the telemeter performance. A white paper calculation has been presented to package the insect telemeter ASIC, along with 10cm antenna directly over 80mg, 5mmX5mmX1mm silver oxide battery to yield a 95mg complete telemeter package, making it to be the world’s smallest and the lightest VHF radio telemeter.
Keywords: Radio frequency identification systems; Telemeter; Insects; Bees; Radio tracking; 400913 Radio frequency engineering